Characterization of small PRESAGE® samples for measurements near the dosimeter edges. (August 2019) - Costa, Filipa; Doran, Simon; Adamovics, John; Nill, Simeon; Hanson, Ian M; Oelfke, Uwe
Abstract: Measurements near the edges of PRESAGE® 3D dosimeters will be important for validating the electron return effect (ERE) that can occur at tissue-air interfaces during radiotherapy treatment delivered with the Elekta MR-linac. We investigate and characterize the spatially non-uniform response of small samples of PRESAGE® to radiation in a conventional linac. We develop a correction to compensate for these non-uniformities and obtain dose values near the dosimeter edges. Five samples from the same batch were uniformly irradiated in a water tank with a broad beam. The non-uniform response of the samples to radiation was investigated and a radial dose-correction function was generated from each sample to obtain a correction image. We then applied these correction images to another sample from the same batch, irradiated with four beams in an inhomogeneous medium, and compared this with the relevant simulated data. Additionally, we irradiated samples after physically removed their edges (axially and top and bottom edges). Higher sensitivity to radiation was observed at the edges ( 6mm) of the samples in comparison with the central region. Applying the dose correction function improved agreement between simulations and measurements, but only partial correction was possible. A uniform response was observed on the samples with the edges removed, which we propose as the best option to measure dose at the edges of PRESAGE® samples.